Law's dream of a common knowledge - Valverde, Mariana, 1955- (Cultural lives of law., 2003)
If knowledge is power, then the power of law can be studied through the lens of knowledge. This book opens up a substantive new area of legal research--knowledge production--and presents a series of case studies showing that the hybridity and eclecticism of legal knowledge processes make it unfruitful to ask questions such as, "Is law becoming more dominated by science?" Mariana Valverde argues that legal decision making cannot be understood if one counterposes science and technology, on the one hand, to common knowledge and common sense on the other. The case studies of law's flexible collage